Assessment of energy performance and GHG emissions for the urban water cycle toward sustainability. Issue 1 (20th December 2022) - Muhammetoglu, Ayse; Al-Omari, Abbas; Al-Houri, Zain; Topkaya, Bulent; Tumbul, Tugba; Muhammetoglu, Habib
Abstract: This study presents a holistic approach to evaluate energy performance and greenhouse gas (GHG) emissions from urban water supply and sanitation stages, which are important for sustainable water management and climate change mitigation. The study was conducted for Antalya city of Turkey to compare baseline and improved scenario conditions using the Energy Performance and Carbon Emissions Assessment and Monitoring (ECAM) tool. The current application of urban water and wastewater services was defined as the baseline scenario. For the improved urban water cycle, the reduction of non-revenue water, onsite sanitation prevention, increase in energy efficiency, biogas production and reuse of treated wastewater were investigated. Water supply and sanitation stages contributed to approximately 26 and 74% of total GHG emissions and 70 and 30% of energy consumption for the baseline scenario, respectively. GHG emissions were determined approximately as 52, 423 tCO2 eq/year for CO2 (40%), 47, 029 tCO2 eq/year for CH4 (35%) and 33, 006 tCO2 eq/year for N2 O (25%) for the baseline scenario. The total GHG emissions of 132, 457 tCO2 eq/year and energy consumption of 136, 328 MWh/year were reduced by 27.65% for GHG emissions and 16.48% for energy consumption for the improved urban water cycle. The outcomes of this research are expected to achieve sustainable cities and combat climate change. HIGHLIGHTS: Energy performance and carbon emission assessment and monitoring study for the urban water cycle is conducted. The baseline condition and improved water supply and sanitation stages are assessed. Impacts of non-revenue water, onsite sanitation reduction and treated wastewater reuse on GHG emissions are investigated. Energy and carbon footprint analyses are performed. GHG emissions, energy performance and service level indicators for wastewater collection and treatment are examined. Graphical Abstract